Neslovanske besede v bovškem narečnem besedišču - Ivančič Kutin, Barbara (Slavistična revija, 2008)
The autor focused on borrowed words in the Bovec dialectal lexicon by implementing a two-faceted approach. The firs part of the article includes dialectal terms for human diseases, excerpted from Slovar bovškega govora Dictionary of Bovec dialect. Based on this material the autor attempts to determine, first, the share of Slovene lexicon and lexicon known in central Slovene dialects, and, secondly, the share of the borrowed wonds maintaining asimilar form in the Bovec dialect as they have in the original language. In the second part, using a comparative method, she attempts to determine what share of Romance (Italian and Friulian) calques and words from the dialects inthe Videm/Udine and Gorica/Gorizia regions (according to Skubic's material) is also known in the Bovec dialect.
Keywords: Bovško; dialektologija; furlanščina; italijanščina; slovenska narečja; slovenščina